Optimal control of ground reaction force and the individual optimization of performance during 100m sprint - Yiu, Y.; Zhou, S. J.; Chen, J. G. (2001)
The purpose of this study is to optimize the individual sport performance during the 100m sprint by the optimal control of ground reaction force. The subject was a national level athlete, best performance 10.65s. Kistler force platform (sample rate 600Hz) and LOCAM Hi-speed camera (150Hz) was used to synchronously record the ground reaction force and the movement of the subject during the maximal speed phase. According to the Impulse-Momentum theory the relationship between the velocity of the c.m. and the ground reaction force can be found. Applying optimization theory and algorithms the ground reaction force was altered reasonably, in order to increase the velocity of the c.m. during each support phase as much as possible. The object of optimization is to maximize the impulse of the ground reaction force, while not changing the support time, the time of positive and negative impulse and the maximal and minimal force values. One dimensional search method in optimization algorithms was used to obtain the optimal solution. Based on the experimental data, we found that the final velocity of the c.m. during support at each step can be increased 0.05m/s through optimal control of ground reaction force. Assuming that the maximal speed phase includes 20 steps, the performance of the subject for 100m could therefore be improved approximately 0.06-0.08s. This improvement is achieved only by changing the patterns of ground reaction force, and the condition of the athlete kept unchanged. In other words, it is obtained by rational force generation.